2018
DOI: 10.1136/oemed-2018-105160
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of heat shock protein 70 (HSP70) polymorphisms and occupational hazards increases the risk of hypertension in coke oven workers

Abstract: Collectively, these data indicate that HSP70 polymorphisms interact with occupational hazards might increase the risk of hypertension in coke oven workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Recent studies have demonstrated that the expression of HSP70 increased in cerebral, myocardial and renal ischemia [29][30][31]. Furthermore, HSP70 was related to the pathogenesis of hypertension and associated diseases [17,19] and there were high levels of HSP70 in serum, plasma and placental tissue of PE patients [20].…”
Section: Rs2227956mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have demonstrated that the expression of HSP70 increased in cerebral, myocardial and renal ischemia [29][30][31]. Furthermore, HSP70 was related to the pathogenesis of hypertension and associated diseases [17,19] and there were high levels of HSP70 in serum, plasma and placental tissue of PE patients [20].…”
Section: Rs2227956mentioning
confidence: 99%
“…As a stress protein, HSP70 plays a pivotal role in protecting cells against apoptosis, oxidative damage and genetic damage [17]. Placental ischemia, oxidative stress and maternal systemic inflammatory response, which play important roles in the pathogenesis of PE, have been shown to induce the expression of HSP70 [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to lung injury, coke oven emissions also have adverse effects on the cardiovascular system. Therefore, more effective measures are needed to protect the health of coke oven workers [19,20]. High levels of 4-OHPh combined with longer working years or being overweight had a joint effect on the risk of diabetes.…”
Section: Organ Dysfunctions and Diseases Of Coke Oven Workersmentioning
confidence: 99%